SATIRE LANGUAGE STYLE BY BU TEJO IN THE SHORT FILM “TILIK” - Nawang Asri Ayuningtyas; Sulis Triyono (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
The use of satire language style by a film creator aims to convey meaning to the public. This study aims at analyzing the use of satire language styles used by Bu Tejo in a short film entitled